Abdominal aortic aneurysm volume and relative intraluminal thrombus volume might be auxiliary predictors of rupture—an observational cross-sectional study - Koncar, I.; Nikolic, D.; Milosevic, Z.; Bogavac-Stanojevic, N.; Ilic, N.; Dragas, M.; Sladojevic, M.; Markovic, M.; Vujcic, A.; Filipovic, N.; Davidovic, L. (Frontiers in Surgery, 2023)
Objectives: The study aimed to identify differences and compare anatomical and biomechanical features between elective and ruptured abdominal aortic aneurysm (AAA) . Methods: Data (clinical, anatomical and biomechanical) of 98 patients with AAA, 75 (76.53%) asymptomatic (Group aAAA) and 23 (23.46%) ruptured AAA (Group rAAA), were prospectively collected and analyzed. Anatomical, morphological, biomechanical imaging markers like peak wall stress (PWS) and rupture risk equivalent diameter (RRED), comorbid conditions and demographics were compared between the groups. Biomechanical features were assessed by analysis of DICOM images by A4Clinics, Vascops and anatomical features were assessed by 3Surgery, Trimensio. Binary and multiple logistic regression analysis were used and adjusted for confounders. Accuracy was assessed using receiving operative characteristic (ROC) curve analysis. Results: In a multivariable model, including gender and age as confounder variables, maximal aneurysm diameter (MAD,OR= 1.063), relative intraluminal thrombus (rILT,OR=1.039) and total aneurysm volume (TAV,OR=1.006) continued to be a significant predictors of AAA rupture with peak wall stress (PWS,OR=1.010) and rupture risk equivalent diameter (RRED,OR=1.031). AUC values and correct classification (cc) for the same parameters and model that combines MAD, TAV and rILT were measured: MAD (0.790, cc=75%), PWS (0.713, cc=73%), RRED (0.717, cc=55%), TAV (0.756, cc=79%), rILT (0.656, cc=60%) and MAD+TAV+rILT (0.797, cc=82%) Conclusion: : Based on our results, besides MAD, other important predictors of rupture that might be used during aneurysm surveillance are TAV and rILT. Biomechanical parameters (PWS, RRED) as valuable predictors should be assessed in prospective clinical trials. Similar studies on AAA smaller than 55mm in diameter, even difficult to organize, would be of even greater clinical value.